2004
DOI: 10.1128/jb.186.15.4940-4950.2004
|View full text |Cite
|
Sign up to set email alerts
|

Two Biosynthetic Pathways for Aromatic Amino Acids in the Archaeon Methanococcus maripaludis

Abstract: Methanococcus maripaludis is a strictly anaerobic, methane-producing archaeon. Aromatic amino acids (AroAAs) are biosynthesized in this autotroph either by the de novo pathway, with chorismate as an intermediate, or by the incorporation of exogenous aryl acids via indolepyruvate oxidoreductase (IOR). In order to evaluate the roles of these pathways, the gene that encodes the third step in the de novo pathway, 3-dehydroquinate dehydratase (DHQ), was deleted. This mutant required all three AroAAs for growth, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 68 publications
3
37
0
Order By: Relevance
“…3. Enzyme systems in M. maripaludis that are expected to require lowpotential electron donors in addition to FMD include CODH-ACS, which catalyzes the biosynthesis of acetyl-CoA from methyltetrahydromethanopterin and CO 2 ; POR, which catalyzes the reductive carboxylation of acetyl-CoA (14, 15); 2-ketoglutarate oxidoreductase, which catalyzes the reductive carboxylation of succinyl-CoA; and branched-chain VOR and two indole-pyruvate oxidoreductases, which are involved in biosynthesis of amino acids from the corresponding carboxylic acids (7,19). In addition, the genome of M. maripaludis contains an oxidoreductase of unknown specificity (9) which could also be coupled to Ehb.…”
Section: Discussionmentioning
confidence: 99%
“…3. Enzyme systems in M. maripaludis that are expected to require lowpotential electron donors in addition to FMD include CODH-ACS, which catalyzes the biosynthesis of acetyl-CoA from methyltetrahydromethanopterin and CO 2 ; POR, which catalyzes the reductive carboxylation of acetyl-CoA (14, 15); 2-ketoglutarate oxidoreductase, which catalyzes the reductive carboxylation of succinyl-CoA; and branched-chain VOR and two indole-pyruvate oxidoreductases, which are involved in biosynthesis of amino acids from the corresponding carboxylic acids (7,19). In addition, the genome of M. maripaludis contains an oxidoreductase of unknown specificity (9) which could also be coupled to Ehb.…”
Section: Discussionmentioning
confidence: 99%
“…In the methanogenic archaea Methanobacterium autotrophicum and Methanococcus maripaludis, novel ferredoxindependent carboxylases were identified that are linked to biosynthetic pathways. Apart from the well-studied pyruvate: ferredoxin oxidoreductase and ␣-ketoglutarate:ferredoxin oxidoreductase, those organisms also employ ␣-keto-isovalerate:ferredoxin oxidoreductase and indolepyruvate:ferredoxin oxidoreductase homologs for the biosynthesis of branched amino acids (e.g., valine) and aromatic amino acids (e.g., tryptophan and phenylalanine) (96,116).…”
Section: Carboxylases In Biosynthetic Pathwaysmentioning
confidence: 99%
“…The enzyme was discovered in 1965 (Cotton and Gibson, 1965) and was initially characterized in bacteria, including several pathogens, as well as in archaea, yeast, fungi and plants ( Fig. 2) (Bode et al, 1984;Fiske and Kane, 1984;Jensen et al, 1988;Porat et al, 2004;Warpeha et al, 2006). The PDT plays a key role in the biosynthesis of L-Phe in organisms that utilize the shikimate pathway (Bentley, 1990;Lingens, 1976).…”
Section: Introductionmentioning
confidence: 99%